2018
DOI: 10.22616/erdev2018.17.n048
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of mechanical parameters of sprayer boom

Abstract: The sprayer boom is a large and complex structure, used to support the spray nozzles. It is important to control and minimize the vibration of the structure on the vertical and horizontal planes, in order to insure the uniformity of pulverization over the field. Owing to the large spray boom widths, flexible behaviour of spray booms becomes important. Even small deformations of the structure can cause, by the large spray boom width, considerable displacements at the boom tips. However, there is not a clear cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…A more rigid structure would yield closer results between the models. Corroborating the observations of Engel ( 2008) and Manea et al (2018), the authors found that the horizontal deformations of the bars contributed to increased oscillation amplitudes. However, the rigid-body motions of the suspension cannot be neglected in this orientation.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…A more rigid structure would yield closer results between the models. Corroborating the observations of Engel ( 2008) and Manea et al (2018), the authors found that the horizontal deformations of the bars contributed to increased oscillation amplitudes. However, the rigid-body motions of the suspension cannot be neglected in this orientation.…”
Section: Resultssupporting
confidence: 59%
“…According to Herbst et al (2018), there is no standard method to test the accuracy of sprayer boom suspensions objectively. Different modeling techniques have been used to represent suspension systems and sprayer booms, such as those based on undeformable bodies (Pontelli et al, 2010 and2009;Tahmasebi et al, 2018) and those based on deformable elements (Koc, 2015;Manea et al, 2018). Alternative modeling was presented by Bjornsson et al (2013), with rigid segments connected by torsional springs to represent the horizontal stiffness of the bar.…”
Section: Introductionmentioning
confidence: 99%
“…The 70-day monitoring values of the four monitoring points of K3+950 monitoring section were imported into the initial training sample as an input vector and four mechanical parameters were output. The results were as follows: η1 =7.11×10 17 Pa·s, E1 =39 Pa, η2 =1.27×10 16 Pa·s and G2 =1.80×10 11 Pa. Other mechanical parameters required for the establishment of the rheological model are shown in Table 3. The inversion parameters were imported into the calculation model, and the rheological displacement of each monitoring point in the section for 70 days was obtained through numerical simulation.…”
Section: Mechanical Parameter Inversion and Rationality Verificationmentioning
confidence: 99%
“…A large number of experimental studies show that the mechanical parameters of the deep buried surrounding rock show significant attenuation characteristics with the increase of strain from the rheological attenuation stage to the acceleration stage [7][8][9][10][11]. However, the existing models for predicting the long-term stability of surrounding rocks all take mechanical parameters as constants for calculations and their models can only be applied to environments where the depth of surrounding rocks is relatively shallow.…”
Section: Introductionmentioning
confidence: 99%
“…The agricultural activities subjected to this research were carried out in the field [1, 3, 7-10, 13, 14], in the greenhouses [2], or in the nurseries and were: herbicide spraying [1,3,8,14,22] and harvesting of heavy products (such as pumpkins) [9].…”
Section: Introductionmentioning
confidence: 99%